EFFECT OF SALINITY CHANGES ON METHIONINE CONTENT IN TIGER GROUPER JUVENILE (Epinephelus fuscoguttatus) - Muhammadar Abdullah Abbas; Muchlisin Zainal Abidin; Dedi Fazriansyah Putra; Firdus Firdus; Agung Setia Batubara; Asmawati Muhammad Sail; Syafruddin Syafruddin; Roslizawaty Roslizawaty; Amalia Sutriana; Dwinna Aliza (Universitas Syiah Kuala, 2018)
This study was conducted to determine the effect of water salinity changes on methionine content in tiger grouper juvenile (Epinephelus fuscoguttatus). A total of 2,560 tiger grouper juveniles were used and divided into five groups consist of 1 control group (without exposed to salinity changes) and 4 treatment groups. The salinity was changed every 2, 3, 4, and 6 hours in treatment A, B, C, and D, respectively. Salinity levels were changed during 24 hours by lowering salinity level from 32 psu to 22 psu. Twenty five of fish were collected from each treatment for methionine content analysis. Data were analysed using one way analysis of variance (ANOVA). The results showed that there was a decrease in methionine content in all treatments. A significant decrease (P0.05) of methionine content in treatment A, B, and C were observed after 20 hours (1.15%), 18 hours (1.27%), and 16 hours (1.24%), respectively. While at 0 hours (control), the methionine content was 2.02%. Methionine level in treatment D was not significantly different (P0.05) compared to control group. As conclusion, rearing the tiger grouper juvenile with salinity fluctuations every 6 hours did not lead to methionine deficiency.